DETERRENCE OF THEFT IN A SITUATION OF COMPETITION BETWEEN FORMAL AND INFORMAL INSTITUTIONS - Yerbanga, Antoine (L'Actualité économique, 2020)
The aim of this article is to highlight important factors neglected in modelling the effects of deterrent policies on thieves' activities in the real world. The methodology adopted consists of defining a world with three continuous spaces. Space in the centre has no institutions and no production. Only the other two spaces have institutions and are places for production. The study uses the Tullock contest fonction for n-players developed by Jia (2012) to identify thieves' efforts and the institutions' endowments at equilibrium. In contrast to the existing literature, our results indicate a perverse, indirect effect of institutions' deterrence strategies on thieves' activities and a negative effect of an increase in institutional deterrence on the total proportion of production stolen. This outcome therefore supports deterrence policies. Symmetric equilibrium becomes unstable when institutions have different production levels. However, we note that asymmetric equilibrium remains optimal, even in situations of differences in production across institutions. A confrontation between thieves from different areas can be a way for an institution to provide less deterrence in an asymmetric balance while guaranteeing a higher level of consumption than that under the opposing institution.